Removal of Propylparaben in an Aqueous System using Magnetite-Silica Ferrofluids of Hydrophobic Deep Eutectic Solvent - Falahudin, Aswin; Insin, Numpon (Applied Science and Engineering Progress, 2024)
A novel sorbent based on ferrofluid hydrophobic deep eutectic solvent magnetite silica (Fe3O4@SiO2@mSiO2- HDES) was successfully synthesized by adding menthol-fatty acid as carrier liquid onto Fe3O4@SiO2@mSiO2 composite. The crystallinity, morphological, functional group and magnetic properties of the materials were characterized by x-ray diffraction, scanning electron microscopy-EDX, Brunauer–Emmett–Teller, vibrating sample magnetometer, thermogravimetric analysis and Fourier Transform-infrared spectroscopy. The adsorption performance of parabens was evaluated as model water pollutants. The Fe3O4@SiO2@mSiO2-HDES ferrofluid was used as a ferrofluid sorbent of parabens prior to spectrophotometry UV-Vis. The effect of several contribution parameters was optimized including ferrofluid volume, pH, stirring time and ionic strength. Under the optimum conditions, a combination of Fe3O4@SiO2@mSiO2-menthol/palmitic acid was achieved as the best ferrofluid with % removal values ranging from 81.00% to 98.62%. The ferrofluid Fe3O4@SiO2@mSiO2-HDES demonstrated high efficiency for the adsorption paraben in the water system which suggests a great potential alternative method for the adsorption of water contaminants in the aquatic system.